The Effect Of Management And Use Of Village Funds And Village Government Accountability And Village Economic Growth In Kupang Tengah District, Kupang Regency - Anthon Simon Yohanis Kerihi; Linda Lomi Ga; Sarina Joyce Margaret Rafael (CV. AFDIFAL MAJU BERKAH, 2023)
Village funds will encourage the implementation of village autonomy, as well as an effort to empower village governments and village communities. the provincial government and district government as facilitators, facilitating village communities to be able to carry out village development. Village funds are a source of village income whose accountability is included in public financial accountability. This study aims to: (1) determine the influence of village fund management on village economic growth in Kupang Tengah District; (2) Knowing the effect of using village funds on village economic growth in Kupang Tengah District, (3) Knowing the effect of village government accountability on village economic growth in Kupang Tengah District, and (4) Knowing the effect of village fund management, village fund utilization and government accountability village on village economic growth in Kupang Tengah District. This study uses a quantitative descriptive approach, with data collection techniques in this study using a questionnaire. The population and sample of this study used a purposive sampling method. This study involved village officials who managed village, sub-district and community fund allocations in the village, with a sample of 32 respondents from 7 villages. SPSS research analysis tool version 25. The results show partially that village fund management influences village economic growth, village fund utilization affects village economic growth, and village government accountability influences village fund growth. Simultaneously, the magnitude of the influence of village fund management, village fund utilization and village government accountability on village economic growth is 66.2%. This means that the management of village funds, the use of village funds, and the accountability of the village government can increase village economic growth in Kupang Tengan District, Kupang Regency.